2018
DOI: 10.1016/j.apcatb.2017.09.071
|View full text |Cite
|
Sign up to set email alerts
|

Role of CuO in the modification of the photocatalytic water splitting behavior of TiO2 nanotube thin films

Abstract: The role of CuO nanoparticles decorating TiO 2 nanotubes (TNT) thin film photoanodes in the behavior of photoelectrocatalytic (PEC) cells for water splitting reaction is investigated. CuO is present mainly as small nanoparticles of few nanometer decorating the internal walls of the TiO 2 nanotubes. Their presence improves i) the photocurrent behavior, ii) the H 2 generation rate by water splitting in a full PEC device (without application of a bias) and iii) the solar-to-hydrogen (STH) efficiency. The increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 162 publications
(67 citation statements)
references
References 69 publications
1
59
0
1
Order By: Relevance
“…As the photoanode for water oxidation, a Ti/NtTiO 2 /CuO electrode wasu sed, for which preparation and characteristics were earlier reported. [21] The photoanodei s characterized by the presence of an array of vertically-aligned TiO 2 nanotubes, which are doped by CuO nanoparticles.T he TiO 2 nanotube film is grown by anodic oxidation on ap erformed Ti thin foil, acting also as electron collector.T he electrons generated by irradiation of this photoanode are collected through this Ti foil and transported on the cathodic part of the cell. The protons generated from the water photo-oxidation diffuse along the TiO 2 nanotubes and reach the Nafion membrane,w hich is joined (by hot pressing) to this Ti/NtTiO 2 /CuO photoanode.…”
Section: Electrocatalytic Reduction Of Co 2 Using Ag Dl/cu 2 O Electrodementioning
confidence: 99%
See 1 more Smart Citation
“…As the photoanode for water oxidation, a Ti/NtTiO 2 /CuO electrode wasu sed, for which preparation and characteristics were earlier reported. [21] The photoanodei s characterized by the presence of an array of vertically-aligned TiO 2 nanotubes, which are doped by CuO nanoparticles.T he TiO 2 nanotube film is grown by anodic oxidation on ap erformed Ti thin foil, acting also as electron collector.T he electrons generated by irradiation of this photoanode are collected through this Ti foil and transported on the cathodic part of the cell. The protons generated from the water photo-oxidation diffuse along the TiO 2 nanotubes and reach the Nafion membrane,w hich is joined (by hot pressing) to this Ti/NtTiO 2 /CuO photoanode.…”
Section: Electrocatalytic Reduction Of Co 2 Using Ag Dl/cu 2 O Electrodementioning
confidence: 99%
“…[50] Thus, there are not specific studies on hybrid Cu 2 O-Cu/GDL electrodes for the electrocatalytic reduction of CO 2 .T herefore, this work reports first their use as electrodes for the electrocatalytic reduction of CO 2 ,a nd then their use in ac ompactdesign PECc ell in combination with the CuO/NtTiO 2 photoanode, which wasp reviously reported for use in water splitting. [21] Results and Discussion Cu 2 O/GDLand Cu/GDL electrodecharacterization AG DL was used as the support for depositing copperb ecause it allows operating the reduction of CO 2 with or without a liquid electrolyte. Different behaviors in CO 2 reduction could be obtainedi nt he two cases, even using the same electrolyte, owing to different surface concentrations of CO 2 and the absence of the electrolyte in the second case.…”
Section: Introductionmentioning
confidence: 99%
“…A general advantage of all vertically aligned nanotubes grown by anodic oxidation is that they offer a direct electron pathway to a back contact (in contrast to particle‐like nanostructures). Therefore, throughout the past decades, TiO 2 nanotubes, specifically conventional CP TiO 2 nanotubes, have been extensively studied for a wide range of applications where this direct electrode contact is beneficial, such as dye‐sensitized solar cells,, fuel cells,, Li‐ion batteries,, photocatalysts,, bio‐applications, and sensors . As SP NTs have been only recently introduced, relatively little is known about their properties – particularly their photoelectrochemical properties, in comparison to conventional close‐packed tubes.…”
Section: Introductionmentioning
confidence: 99%
“…It indicated that CuO@NH 2 ‐MIL‐125(Ti)/NF showed a superior catalytic activity towards HER as compared to all other synthesized samples. As reported previously in literature that CuO was a promising p‐type semiconductor material and had very attraction for light harvesting applications in visible region due to narrow band gap (1.2 to 1.7 eV) . So, in CuO@NH 2 MIL‐125(Ti), it facilitated better charge separation due to synergistic effect and hetro‐junction formation between CuO nanoparticles and amine functionalized MOF NH 2 ‐MIL‐125(Ti).…”
Section: Hydrogen Evolution Reaction Studiesmentioning
confidence: 99%